Nb-doped and P2 / O3 dual-phase composite modified sodium-ion battery ternary positive electrode material and preparation method thereof

By introducing Nb elements into the positive electrode material of sodium ion battery and building a P2/O3 biphase composite structure, the problems of poor cycle stability and low energy density of existing materials are solved, and higher electrochemical performance and lower environmental impact are achieved.

CN119725518AInactive Publication Date: 2025-03-28GUANGXI UNIV

Patent Information

Application Number
CN202411900910.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing sodium ion battery layered oxide positive electrode materials have problems such as poor circulation stability, low energy density, and poor air stability, and it is difficult to compete with lithium-ion batteries.

Method used

By combining co-precipitation method and high-temperature sintering method, Nb elements were introduced and reaction conditions were controlled to obtain a ternary positive electrode material of sodium ion battery doped with P2/O3 biphase composite.

Benefits of technology

The cycling stability, rate performance and air stability of the layered ternary cathode material of sodium ion battery are significantly improved, and there is no Co doping, which has little adverse effects on the environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725518A_ABST
    Figure CN119725518A_ABST
Patent Text Reader

Abstract

The invention provides an Nb-doped and P2 / O3 double-phase composite modified sodium-ion battery ternary positive electrode material and a preparation method thereof, and belongs to the technical field of new energy material sodium-ion battery positive electrode materials, and the Nb-doped and P2 / O3 double-phase composite positive electrode material is obtained by combining a coprecipitation method and a high-temperature sintering method, introducing an Nb element and controlling reaction conditions. According to the prepared battery positive electrode material, a strong synergistic effect exists between Nb doping and a P2 / O3 double-phase structure, the structural stability is remarkably improved, side reactions are effectively inhibited, the cycle performance and the rate performance are excellent, Co doping is avoided, and the adverse effect on the environment is small.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a sodium ion battery ternary positive electrode material doped with Nb and compositely modified with P2 / O3 in two phases and a preparation method thereof, belonging to the technical field of new energy material sodium ion battery positive electrode materials. Background Art

[0002] Since the beginning of the 21st century, with the rapid development of the economy and society, people's demand for energy has continued to rise. Non-renewable energy sources such as coal, oil, and natural gas are the three major energy sources on which human beings depend for survival, but their reserves on the earth are limited, and the energy crisis is imminent. Today, sustainable clean energy such as hydropower, wind power, and solar energy are being rapidly developed to meet energy needs worldwide. Due to the dependence of these renewable energy sources on seasons and weather, electric energy storage systems (EES) are crucial to their application. A major focus of developing EES is to explore low-cost, high-reliability, long cycle life, and high-safety batteries. Lithium-ion batteries (LIBs), as a mature commercial energy storage battery, have been widely used in consumer electronics, computers, communications, electric vehicles, and other fields, but their development has been severely restricted due to the limited reserves and uneven distribution of lithium resources. Therefore, there is an urgent need to find a new type of energy storage secondary battery as a substitute for lithium-ion batteries. Sodium and lithium both belong to the main group of alkali metals and have similar physical and chemical properties. Sodium-ion batteries (SIBs) are considered to be a promising substitute for lithium-ion batteries due to their similar charging and discharging mechanisms and abundant sodium resources in the earth's crust. Although sodium has a larger radius and a higher standard redox potential, which makes sodium-ion batteries have poor cycle stability and slow kinetic performance, making it difficult to compete with lithium-ion batteries, sodium-ion batteries are low-cost, have abundant sodium resources, and have higher safety. In these aspects, sodium-ion batteries are more competitive than lithium-ion batteries.

[0003] As the main component of sodium-ion batteries, cathode materials dominate battery performance in terms of capacity, energy density, cycle performance and total cost. Sodium-ion battery cathode materials are mainly divided into four categories: layered oxides, polyanionic compounds, Prussian blue compounds, and organic compounds. Among the various cathode material options, polyanionic compounds and layered transition metal oxides are the most widely studied materials. Due to the inductive effect of polyanionic groups, polyanionic compounds exhibit higher average voltages. However, the presence of polyanionic groups reduces the weight capacity of electrode materials. More importantly, the low density of the polyanionic structure leads to low volumetric energy density. Layered transition metal oxides generally have high reversible capacities (up to 240 mAh·g −1). In addition, their compact structural framework makes them suitable for applications requiring high volumetric energy density and are considered to be promising cathode materials. Layered oxides have the advantages of high capacity, abundant raw materials, and simple preparation process, but they also have disadvantages such as poor cycle stability, low energy density, and poor air stability. Summary of the invention

[0004] The purpose of the present invention is to overcome the deficiencies in the prior art and provide a sodium ion battery ternary positive electrode material and a preparation method thereof that is Nb doped and P2 / O3 dual-phase composite modified, aiming to improve the electrochemical performance of the sodium ion battery layered oxide positive electrode material by element doping and structural design. The sodium ion battery positive electrode material prepared by the present invention has excellent cycle stability and rate performance, and is free of Co doping, and has less adverse effects on the environment.

[0005] In order to solve the above technical problems, the present invention is implemented by adopting the following technical solutions: A sodium ion battery ternary positive electrode material doped with Nb and modified by a two-phase composite of P2 / O3 and a preparation method thereof, characterized in that the Nb element is introduced by combining a coprecipitation method with a high-temperature sintering method and the reaction conditions are controlled to obtain a positive electrode material doped with Nb and modified by a two-phase composite of P2 / O3.

[0006] It is worth noting that the present invention, through an innovative process method, cleverly realizes the construction of Nb element doping and P2 / O3 dual-phase structure, significantly improving the electrochemical performance of the layered ternary cathode material of the sodium ion battery, including rate performance, cycle stability and air stability. In addition, the preparation method disclosed in the present invention is simple and efficient, the required raw materials are widely available, the cost is low, and it is easy to realize industrial large-scale production. The comprehensive performance of the obtained material is significantly better than that of the traditional unmodified layered ternary cathode material.

[0007] Furthermore, the specific steps of the preparation method include: (1) mixing the ternary precursor with a niobium source through an ethanol solution, heating, evaporating, and drying to obtain a ternary precursor pretreated with niobium; (2) The ternary precursor after niobium pretreatment is mixed with a sodium source and ball-milled, and then sintered at high temperature under a protective atmosphere. During the sintering process, the heating rate, sintering temperature and sintering time are controlled, and then naturally cooled to room temperature to obtain a ternary positive electrode material doped with niobium and a P2 / O3 dual-phase composite.

[0008] Compared with the single element doping or simple structure control scheme in the prior art, the present invention innovatively combines Nb doping with P2 / O3 dual-phase composite to achieve synergistic optimization of multiple performance aspects. There is a close synergistic effect between the doping of Nb element and the P2 / O3 dual-phase structure, which can effectively improve the key properties of the material such as crystal structure stability, sodium ion diffusion kinetics and surface chemical stability, thereby comprehensively improving the electrochemical performance of the material.

[0009] Furthermore, in step (1), the ternary precursor is Ni x Fe y Mn 1-x-y CO3, where 0.2 ≤ x <0.4,0.2< y ≤0.4; the niobium source is one or both of ammonium niobate oxalate hydrate and niobium pentoxide.

[0010] Furthermore, the mass of the niobium source accounts for 0.1%-5% of the mass of the ternary positive electrode material.

[0011] Furthermore, in step (2), the sodium source is one or both of sodium carbonate and sodium hydroxide.

[0012] It is worth noting that the various metal sources selected in the present invention can accurately control the elemental composition of the layered ternary cathode material and provide a stable electrochemical active center for the material. Among them, the introduction of the Nb source can not only participate in the construction of the crystal structure and stabilize the lattice structure, but also affect the electronic structure and redox activity of the transition metal ions to a certain extent, thereby improving the overall performance of the material.

[0013] Furthermore, the molar ratio of Na in the sodium source to Ni+Fe+Mn in the ternary precursor is (0.44-1.05):1.

[0014] Furthermore, in the step (2), the ball milling speed is 100-500 rpm, the ball milling time is 0.1-100 h, and the ball-to-material ratio is 10:1-100:1.

[0015] It is worth noting that different proportions of the molar ratio of Na in the sodium source to Ni+Fe+Mn in the ternary precursor, the ball milling speed and the ball milling time can regulate the layered structure of the material after sintering, obtain two-phase structures in different proportions, and thus obtain positive electrode materials with good electrochemical properties.

[0016] Furthermore, in the step (2), the calcination is a one-step calcination, wherein the calcination heating rate is 2-6 °C / min, and the protective atmosphere is one or both of air and oxygen.

[0017] Furthermore, in the step (2), the calcination temperature ranges from 800 to 1000°C, and the calcination time ranges from 8 to 24 hours.

[0018] It is worth mentioning that suitable calcination temperature conditions can ensure the formation of a uniform crystal structure during the high-temperature sintering process, thereby obtaining a Nb-doped and P2 / O3 dual-phase composite sodium-ion battery layered ternary positive electrode material with excellent performance.

[0019] The second object of the present invention is to provide a Nb-doped and P2 / O3 two-phase composite sodium ion battery layered ternary positive electrode material prepared by the preparation method as described above.

[0020] The chemical formula of a sodium ion battery ternary cathode material doped with Nb and modified with P2 / O3 dual-phase composite is: Na b Ni x Fe y Mn 1-x-y (Nb) z O2, where 0.20≤ x <0.50,0.20< y ≤0.50,0.002≤ z ≤0.10,0.44≤ b ≤1.00. There are both P2 phase and O3 phase in the material. According to XRD spectrum analysis, the characteristic peaks of P2 phase and O3 phase are obvious, and the proportion of P2 phase is 0%-100%, and the proportion of O3 phase is 0%-100%.

[0021] It is worth noting that the Nb-doped and P2 / O3 dual-phase composite sodium-ion battery layered ternary positive electrode material obtained by the present invention has achieved a comprehensive improvement in material performance through unique element composition and structural design. The doping of the Nb element effectively stabilizes the lattice structure, inhibits the migration and phase change of transition metal ions, and improves the structural stability of the material. At the same time, the presence of the P2 / O3 dual-phase structure provides a variety of diffusion channels for sodium ions, optimizes the diffusion kinetics of sodium ions, and enables the material to maintain good structural integrity and electrochemical reversibility during the charge and discharge process. In addition, the chemical stability of the material surface has also been significantly improved, reducing side reactions with the electrolyte and improving the cycle life and air stability of the battery.

[0022] Compared with the prior art, the beneficial effects achieved by the present invention are: 1. The Nb-doped and P2 / O3 dual-phase composite modified sodium ion battery ternary positive electrode material obtained by the present invention significantly promotes Na +The diffusion kinetics of the cathode material are improved, which improves the cycle stability and rate performance of the cathode material. Among them, the specific capacity of the sodium ion battery ternary cathode material doped with Nb and modified with P2 / O3 dual-phase composite is 116.1 mAh·g at 0.1C current. −1 The capacity retention rate after 200 cycles at 1C is 92%, and the specific capacity is 87.3 mAh g at 10C rate. −1 Furthermore, the material of the present invention is free of Co doping and has less adverse impact on the environment.

[0023] 2. Compared with the traditional modification method of layered ternary cathode materials for sodium ion batteries, the present invention adopts the strategy of Nb doping and P2 / O3 dual-phase composite to achieve synergistic improvement of various performance aspects. Nb doping enhances the stability of the crystal structure, inhibits the volume change and microcrack formation of the material caused by phase change, and optimizes the redox activity of transition metal ions. The P2 / O3 dual-phase structure not only provides abundant sodium ion diffusion paths, but also further stabilizes the overall structure of the material through the synergistic effect between the two phases. This synergistic effect significantly improves the cycle stability and rate performance of the battery, while improving the air stability of the material and reducing the risk of performance degradation of the battery in practical applications.

[0024] 3. The preparation method of the present invention has the advantages of simple process and easy operation. Through the two relatively mature process steps of coprecipitation reaction and high-temperature solid-phase sintering, the construction of Nb doping and P2 / O3 dual-phase composite structure can be achieved without complex equipment and harsh process conditions. Moreover, the choice of raw materials is wide and low-cost, which is conducive to large-scale industrial production and provides strong support for the commercial application of layered ternary cathode materials for sodium ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings in the following description are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without creative work. Figure 1 It is a scanning electron microscope image provided by an embodiment of the present invention.

[0026] Figure 2 It is a HRTEM image provided by an embodiment of the present invention.

[0027] Figure 3 It is the X-ray diffraction pattern provided by the embodiment of the present invention, comparative example 1 and comparative example 2.

[0028] Figure 4The first three constant current charge / discharge (GCD) curves of the embodiment at 0.1 C current are shown.

[0029] Figure 5 The first three constant current charge / discharge (GCD) curves of Comparative Example 1 at 0.1 C current.

[0030] Figure 6 The graphs are the cycle performances of Example, Comparative Example 1 and Comparative Example 2 at 1 C current.

[0031] Figure 7 The figure is a rate performance curve diagram of the embodiment, comparative example 1 and comparative example 2 at different current densities of 0.1-10 C. DETAILED DESCRIPTION

[0032] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] The word "embodiment" used here as an "exemplary" does not necessarily mean that any embodiment described is superior to or better than other embodiments. Unless otherwise specified, the performance index tests in the embodiments of this application are performed using conventional test methods in the art. It should be understood that the terms described in this application are only used to describe specific implementation methods and are not used to limit the content disclosed in this application.

[0034] Unless otherwise specified, the technical and scientific terms used in this document have the same meanings as commonly understood by ordinary technicians in the technical field to which this application belongs; other experimental methods and technical means not specifically specified in this application refer to experimental methods and technical means commonly used by ordinary technicians in this field.

[0035] In order to better illustrate the content of the present application, numerous specific details are provided in the specific examples below. It should be understood by those skilled in the art that the present application can also be implemented without certain specific details. In the embodiments, some methods, means, instruments, equipment, etc. well known to those skilled in the art are not described in detail in order to highlight the main purpose of the present application.

[0036] Under the premise of no conflict, the technical features disclosed in the embodiments of the present application can be combined arbitrarily, and the resulting technical solutions belong to the contents disclosed in the embodiments of the present application.

[0037] The present invention provides a sodium ion battery ternary positive electrode material modified by Nb doping and P2 / O3 dual-phase composite and a preparation method thereof, belonging to the technical field of new energy material sodium ion battery positive electrode material. By combining a coprecipitation method with a high-temperature sintering method, the Nb element is introduced and the reaction conditions are controlled to obtain a positive electrode material doped with Nb and composited with P2 / O3 dual phases. There is a synergistic effect between Nb doping and the P2 / O3 dual-phase composite structure. After the Nb element enters the lattice, it forms a stronger chemical bond with the transition metal ion, enhances the stability of the crystal structure, and inhibits the volume change of the material and the formation of microcracks caused by phase change. The P2 / O3 dual-phase structure can coordinate with each other during the charge and discharge process, relieve stress accumulation, and maintain the integrity of the material structure, thereby effectively enhancing the structural stability of the material.

[0038] The present invention also provides a sodium ion battery ternary positive electrode material doped with Nb and modified with P2 / O3 dual-phase composite and a preparation method thereof, comprising the following steps: (1) mixing the ternary precursor with a niobium source through an ethanol solution, heating, evaporating, and drying to obtain a ternary precursor pretreated with niobium; (2) The ternary precursor after niobium pretreatment is mixed with a sodium source and ball-milled, and then sintered at high temperature under a protective atmosphere. During the sintering process, the heating rate, sintering temperature and sintering time are controlled, and then naturally cooled to room temperature to obtain a ternary positive electrode material doped with niobium and a P2 / O3 dual-phase composite.

[0039] In order to better understand the present invention, the present invention is further specifically described below through the following examples, but it should not be understood as a limitation of the present invention. Some non-essential improvements and adjustments made by technicians in this field based on the above invention content are also considered to fall within the protection scope of the present invention.

[0040] Hereinafter, a Nb-doped and P2 / O3 dual-phase composite modified sodium ion battery ternary positive electrode material and a preparation method thereof are described in detail through specific embodiments of the present invention.

[0041] Example: The preparation method of niobium-doped and P2 / O3 dual-phase composite ternary positive electrode material specifically comprises the following steps: First, a simple coprecipitation method was used to prepare the precursor. First, 50 mL of mixed solution A containing stoichiometric NiSO4·6H2O, MnSO4·H2O and FeSO4·7H2O was prepared, and then solution B containing sodium carbonate was added dropwise to solution A under constant stirring. The concentration, pH, temperature and stirring speed of the solution in the reactor were carefully controlled. The product was heated at 90 °C overnight, filtered, washed, and dried in a vacuum oven at 110 °C for 12 h to obtain [Ni 1 / 3 Fe 1 / 3 Mn 1 / 3]CO3 precursor powder.

[0042] For Nb doping and composite phase P2 / O3−Na 2 / 3 Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 O2−2 wt% Nb, the ammonium niobate oxalate hydrate compound C4H4NNbO9·nH2O, which is less used by researchers, was used as the niobium source. First, C4H4NNbO9·nH2O (0.0201 g) was mixed with [Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ]CO3 precursor (1.005 g) was stirred at 80 °C with alcohol solvent and dried in a vacuum oven at 80 °C for 12 h. A certain stoichiometric ratio of Na2CO3 (0.3709 g), C4H4NNbO9·nH2O and [Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 The ]CO3 precursor mixture was mixed evenly, ground in a ball mill at 300 rpm for 1 h, with a ball-to-material ratio of 10:1, and calcined in a tube furnace at 900 °C for 15 h in an oxygen atmosphere to obtain the product. An excess of 5 mol % Na2CO3 was used to compensate for the volatilization of Na during the calcination process.

[0043] In order to further demonstrate the beneficial effects of the present invention and to better understand the present invention, the properties and application performance of the preparation method of the sodium ion battery ternary positive electrode material doped with Nb and modified with P2 / O3 dual-phase composite disclosed in the present invention are further illustrated by the following comparative examples and performance tests, but it should not be understood as a limitation of the present invention. The properties of the methods obtained by other measurement experiments conducted by technicians in this field according to the above invention content and the applications based on the above properties are also deemed to fall within the protection scope of the present invention.

[0044] Comparative Example 1: The preparation method of the original sample ternary positive electrode material specifically comprises the following steps: For O3−NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2,[Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ]CO3 precursor was treated under the same conditions as in the example (stirring with alcohol at 80 °C and drying overnight). A certain stoichiometric ratio of Na2CO3 (0.55654 g) and [Ni 1 / 3 Fe 1 / 3 Mn 1 / 3]CO3 (1.005 g) precursor was mixed evenly, ground by ball mill at 300 rpm for 1 h, with a ball to material ratio of 10:1, and calcined in a tube furnace at 900 °C for 15 h in an oxygen atmosphere to obtain the product. Excessive 5 mol % Na2CO3 was used to compensate for the volatilization of Na during the calcination process.

[0045] Comparative Example 2: The method for preparing a ternary positive electrode material doped with niobium element specifically comprises the following steps: For O3−NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2−2 wt% Nb, firstly, C4H4NNbO9·nH2O (0.0201 g) and [Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ]CO3 (1.005 g) precursor was stirred at 80 °C with alcohol solvent. It was then dried in a vacuum oven at 80 °C for 12 h. The stoichiometric ratio of Na2CO3 (0.55654 g), C4H4NNbO9·nH2O and [Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 The CO3 precursor mixture was mixed evenly, ground in a ball mill at 300 rpm for 1 h, with a ball-to-material ratio of 10:1, and calcined in a tube furnace at 900 °C for 15 h in an oxygen atmosphere to obtain the product. An excess of 5 mol % Na2CO3 was used to compensate for the volatilization of Na during the calcination process.

[0046] The P2 / O3-Na 2 / 3 Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 O2−2 wt% Nb layered oxide sodium ion battery cathode material composite hydrogen storage material, O3−Na 2 / 3 Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 O2 layered oxide and O3−NaNi of Comparative Example 2 1 / 3 Fe 1 / 3 Mn 1 / 3 O2−2 wt% Nb sodium ion battery cathode material was subjected to morphology analysis, structural characterization and performance testing.

[0047] The present invention uses scanning electron microscopy, X-ray diffraction experiments and electrochemical tests to determine the structure and performance of the sodium ion battery layered oxide positive electrode material.

[0048] in, Figure 1is a scanning electron microscope image provided by an embodiment of the present invention, from Figure 1 It can be seen that P2 / O3−Na 2 / 3 Ni 1 / 3Fe 1 / 3 Mn 1 / 3 The O2−2 wt% Nb layered oxide sodium ion battery cathode material is a micron-sized spherical particle composed of hexagonal particles with a diameter of about 0.3 μm and a thickness of about 100 nm. Figure 2 is a HRTEM image provided by an embodiment of the present invention. The atomic structure of PO-NFM-Nb was studied using a transmission electron microscope (TEM). Figure 2 As shown in Figure 2, high-resolution HRTEM images clearly show lattice fringes, indicating that the prepared material is well crystallized. HRTEM images show the coexistence of P2 and O3 domains in a PO-NFM-Nb grain, and the interplanar spacings of 0.568 and 0.532 nm are determined, corresponding to Figure 2 The (002) crystal plane of the P2 phase and the (003) crystal plane of the O3 phase.

[0049] Figure 3 is the X-ray diffraction pattern provided by the embodiment of the present invention, comparative example 1 and comparative example 2. 1 / 3Fe 1 / 3 Mn 1 / 3 O2, O3−NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 The diffraction peaks of O2−2 wt% Nb can be well compared with α−NaNi 0.5 Mn 0.5 O2 phase (PDF#54−0887, R−3m space group), no other phases were found. 2 / 3 Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 The XRD spectrum of O2−2wt% Nb shows diffraction peaks of both P2 and O3 phase layered structures, which is consistent with the XRD pattern of α−NaNi 0.5 Mn 0.5 O2 phase (PDF#54−0887, R−3m space group) and Na 0.67 Ni 0.33 Mn 0.67 The diffraction peaks are sharp, indicating that the embodiments, comparative examples 1 and 2 have good crystallinity and no other impurity peaks exist.

[0050] Figure 4 The first three constant current charge / discharge (GCD) curves of the embodiment at 0.1 C current are shown. Figure 5 The first three constant current charge / discharge (GCD) curves of Comparative Example 1 at 0.1 C current are shown in Figure 1. Figure 4 Example and Figure 5 Comparison with Example 1, Example P2 / O3-Na 2 / 3 Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 The specific capacity of O2−2 wt% Nb is reduced, but the discharge−charge curves are basically smooth in the 1st to 3rd cycles, indicating that the Na insertion / extraction is a typical solid solution mechanism, and the three initial discharge−charge curves almost completely overlap, showing good reversibility.

[0051] Figure 6 The cycle performance diagrams of the embodiment, comparative example 1 and comparative example 2 at 1 C current are shown in FIG. 1 / 3Fe 1 / 3 Mn 1 / 3 The capacity retention rate of O2 after 200 cycles at 1 C current was 45%, and the capacity retention rate after 400 cycles at 1 C current was 15.6%. 2 / 3 Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 The capacity retention rate of O2−2 wt% Nb after 200 cycles at 1 C current is 92%, and the capacity retention rate after 400 cycles at 1 C current is 69%, which is much better than that of comparative example 1, indicating that the cycle stability of the material can be improved by Nb doping and composite phase.

[0052] Figure 7 The figure is the rate performance curve of Example 1 and Comparative Example 2 at different current densities of 0.1-10 C. Obviously, with the increase of current rate, the polarization of different examples increases and the specific capacity decreases significantly. 2 / 3 Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 O2−2 wt% Nb、O3−NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2, O3−NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 The first discharge capacities of O2−2 wt% Nb are 116.1, 117, and 125 mAh g −1 At current densities of 0.5, 1, 2, 5, and 10 C, P2 / O3−Na 2 / 3 Ni 1 / 3 Fe1 / 3 Mn 1 / 3 O2−2 wt% Nb (discharge capacity of 87.3 mAh·g at 10 C current) −1 , capacity decay rate is 24.8%) and O3−NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2−2 wt% Nb (discharge capacity of 77.5 mAh·g at 10 C current) −1 , the capacity decay rate is 38%), which shows a higher 1 / 3 Fe 1 / 3 Mn 1 / 3 O2 (discharge capacity at 10 C current is 69.9 mAh g −1 , the capacity decay rate is 40.2%) and has a better rate performance. In addition, when the charge and discharge rate returns to 0.1 C, P2 / O3−Na 2 / 3 Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 The capacity retention rate of O2−2 wt% Nb is higher than that of O3−NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2, indicating P2 / O3−Na 2 / 3Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 The O2−2 wt% Nb electrode can better work continuously at different rates between 2.0 and 4.0 V.

[0053] In summary, Nb element doping and P2 / O3 phase composite modification can greatly improve the P2 / O3-Na x Ni 1 / 3Fe 1 / 3 Mn 1 / 3 O2− y Electrochemical performance of wt% Nb layered oxide sodium ion battery cathode material. 2 / 3 Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 O2−2 wt% Nb has the following excellent properties: good cycle stability (the capacity retention rate after 200 cycles at 1C current is 92%), good rate performance (at 10 C current, the discharge specific capacity is still as high as 87.3 mAh·g −1 , capacity decay is 24.8%); and there is no Co doping, so the adverse impact on the environment is relatively small.

[0054] It should be noted that the above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principle of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

[0055] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the technical principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A sodium ion battery ternary positive electrode material doped with Nb and modified with P2 / O3 dual-phase composite and a preparation method thereof, characterized in that: By combining the co-precipitation method with the high-temperature sintering method, the Nb element is introduced and the reaction conditions are controlled to obtain a Nb-doped and P2 / O3 dual-phase composite positive electrode material.

2. The Nb-doped and P2 / O3 dual-phase composite modified sodium ion battery ternary positive electrode material and preparation method thereof according to claim 1, characterized in that: The specific steps include: (1) mixing the ternary precursor with a niobium source through an ethanol solution, heating, evaporating, and drying to obtain a ternary precursor pretreated with niobium; (2) The ternary precursor after niobium pretreatment is mixed with a sodium source and ball-milled, and then sintered at high temperature under a protective atmosphere. During the sintering process, the heating rate, sintering temperature and sintering time are controlled, and then naturally cooled to room temperature to obtain a ternary positive electrode material doped with niobium and a P2 / O3 dual-phase composite.

3. The Nb-doped and P2 / O3 dual-phase composite modified sodium ion battery ternary positive electrode material and its preparation method according to claim 2, characterized in that: In the step (1), the ternary precursor is Ni x Fe y Mn 1-x-y CO3, where 0.2 ≤ x <0.4,0.2< y ≤0.4; the niobium source is one or both of niobium oxalate and niobium pentoxide.

4. The Nb-doped and P2 / O3 dual-phase composite modified sodium ion battery ternary positive electrode material and preparation method thereof according to claim 3, characterized in that: The mass of the niobium source accounts for 0.1%-5% of the mass of the ternary positive electrode material.

5. The Nb-doped and P2 / O3 dual-phase composite modified sodium ion battery ternary positive electrode material and preparation method thereof according to claim 2, characterized in that: In the step (2), the sodium source is one or both of sodium carbonate and sodium hydroxide.

6. The Nb-doped and P2 / O3 dual-phase composite modified sodium ion battery ternary positive electrode material and preparation method thereof according to claim 5, characterized in that: The molar ratio of Na in the sodium source to Ni+Fe+Mn in the ternary precursor is (0.44-1.05):

1.

7. The Nb-doped and P2 / O3 dual-phase composite modified sodium ion battery ternary positive electrode material and preparation method thereof according to claim 2, characterized in that: In the step (2), the ball milling speed is 100-500 rpm, the ball milling time is 0.1-100 h, and the ball-to-material ratio is 10:1-100:

1.

8. The Nb-doped and P2 / O3 dual-phase composite modified sodium ion battery ternary positive electrode material and preparation method thereof according to claim 2, characterized in that: In the step (2), the calcination is a one-step calcination, wherein the heating rate of the calcination is 2-6°C / min, and the protective atmosphere is one or both of air and oxygen.

9. The Nb-doped and P2 / O3 dual-phase composite modified sodium ion battery ternary positive electrode material and preparation method thereof according to claim 8, characterized in that: In the step (2), the calcination temperature ranges from 800 to 1000°C, and the calcination time ranges from 8 to 24 hours.

10. A sodium ion battery ternary positive electrode material prepared by the preparation method according to any one of claims 1 to 9, characterized in that: The chemical formula of the sodium ion battery ternary positive electrode material doped with Nb and modified with P2 / O3 dual-phase composite is: b Ni x Fe y Mn 1-x-y (Nb) z O2, where 0.20≤ x <0.50,0.20< y ≤0.50,0.002≤ z ≤0.10,0.44≤ b ≤1.

00. There are both P2 phase and O3 phase in the material. According to XRD spectrum analysis, the characteristic peaks of P2 phase and O3 phase are obvious, and the proportion of P2 phase is 0%-100%, and the proportion of O3 phase is 0%-100%.

Citation Information

Patent Citations

  • Sodium-rich P2 / O3 biphase layered oxide and preparation method thereof, sodium ion battery positive electrode material and battery

    CN116573683A

  • Double-site metal ion doped nickel iron sodium manganate positive electrode material and preparation method thereof, positive electrode plate and sodium ion battery

    CN118315567A

  • Niobium-doped modified O3 type sodium ion battery positive electrode material and preparation method thereof

    CN118867217A

  • Single-step synthesis of nanostructured thin films by a chemical vapor and aerosol deposition process

    US20160056448A1

Cited By

  • P2 / O3 composite phase sodium ion battery positive electrode material as well as preparation method and application thereof

    CN120757159A